Oracy in English language education insights from practice-oriented research - Reckermann, Julia; Siepmann, Philipp 1984-; Matz, Frauke 1976- (Springer, 2024)
"This book innovatively connects the two fields of oracy and practice-oriented empirical research in English language education. It creates synergies and proposes innovative approaches to the study of oracy in the context of learning and teaching English as a second, additional or foreign language. The book also develops a contemporary and holistic concept of oracy, thus contributing to the theoretical discourse in this area of research. The first part provides a general framework of different approaches to conducting practice-oriented research in English language teaching. It introduces the concept of oracy and discusses its relevance to language teaching. Design-based research and action research are outlined as two practice-oriented research approaches. The second part presents research on how oracy can be fostered and assessed at primary and secondary levels, while the third part focuses on tertiary education. The contributions to this book highlight the opportunities and challenges of conducting research in, on, and for classroom practice with stakeholders such as teachers, students, teacher trainees, university students, parents, and school administrators. They explore selected teaching methods, assessment and, finally, teacher education. The theoretical, methodological, and practical challenges of research-practice partnerships are also addressed. This book demonstrates that innovative approaches to the development and assessment of oral skills can be developed through close collaboration between different stakeholders in language education. It serves as an inspiration for other educators and researchers in the field of English language education at all levels."
Keywords: Englischunterricht; Kommunikative Kompetenz; Mündlichkeit; Aufsatzsammlung